Fatores de influência na qualidade de vida dos profissionais de saúde: uma discussão sobre a qualidade de vida no trabalho - Alves, Adelaide Martins (Universidade Federal do Tocantins, 2023)
Introduction: Quality of Life at Work (QWL) has become an increasingly relevant issue on the agenda of public policy managers, since the planning, development, monitoring and evaluation of policies depend on the efficient use of available resources. Therefore, this research proposed to evaluate studies on Quality of Life at Work in health professionals and to identify which factors most influence the quality of life of these workers. Method: through the analysis of scientific papers published between the years 2017 and 2021, whose guiding question used was: What are the factors of influence on the Quality of Work Life of health professionals. The Scielo (Scientific Electronic Library Online) database was used, in which 81 studies were identified, 18 of which were selected for analysis. Results: in the 18 articles analyzed, 8 factors were identified as influencing Quality of Work Life, which had a total of 40 citations. These factors were: work-related illness; physical environment; organizational environment; external factors related to the user's social vulnerability situation; life habits; work hours; compensation; and satisfaction with the work performed. Conclusion: this study demonstrated that QWL depends on multiple factors, whether intrinsic to the individual and the organization to which he is integrated or extrinsic in relation to his social and extra-organizational context, highlighting the need for periodic studies on the subject in order to subsidize public and private managers in the implementation of the most appropriate measures to reduce the level of dissatisfaction of health professionals with their work.